PARADIGMA PENDIDIKAN SEJARAH DALAM MENGHADAPI TANTANGAN MASA DEPAN - Suswandari Suswandari (LPMPP Universitas Negeri Yogyakarta, 2010)
Abstract: The History Teaching Paradigm Facing Future Challenges. Teaching history is an interesting topic to be discussed, especially when modern human life becomes more materialistic and pays almost no attention to moral values. History, and especially history teaching, as a part of social sciences becomes dry because it provides no financial benefits in the short run as in the case of other social sciences. However, history and history teaching play an important role in the existence of a nation with regard to moral values. By studying history everybody can understand better about himself or herself, his or her existence, and how life always changes through experiences. History teaches people to be wise and not to repeat mistakes. Therefore, history teaching plays an important role in the existence of a nation.Keywords: paradigm, history teaching, future challenges